Development of the portable satellite laser ranging system - Broomhall, Mark Anthony (Curtin University, 2003)
The Portable Satellite Laser Ranger (PSLR) is a light weight, highly portable satellite laser ranging system which employs many of the techniques and equipment types of larger fixed systems. It has a primary telescope aperture of 62 cm and uses a 150 ps pulse of 130 mJ at the second harmonic wavelength of 532 nm. The system is designed to use as little ancillary equipment as possible and only requires one small instrument rack and one PC based control computer. All of the control features of the system are based or installed in the control computer.The PSLR project at Curtin University was concerned with repairing and u p grading the PSLR to return the system to operational capacity. This involved the replacement of missing control components, repair of some hardware, modifications to the control program, and several calibration and operational tests. These tests showed that the PSLR system was capable of a ranging accuracy to fixed targets of 8.5 mm with an average accuracy of 23 mm. They showed that the PSLR was capable, in selective conditions, to track star ephemerides to less than 54. The mount error (standard deviation) over several orientations was shown to be 0.253° in elevation and 0.337° in azimuth.This dissertation will discuss; i) the operation of the equipment used with the PSLR and similar systems, the steps taken to repair or replace the necessary equipment, ii) the tests required to calibrate or evaluate various sub-systems of the PSLR and, iii) the results and conclusions drawn as a result.